Slavery and the Making of America - Horton, James Oliver; Horton, Lois E (New York : Oxford University Press, 2006)
The history of slavery is central to understanding the history of the United States. Slavery and the Making of America offers a richly illustrated, vividly written history that illuminates the human side of this inhumane institution, presenting it largely through stories of the slaves themselves. Readers will discover a wide ranging and sharply nuanced look at American slavery, from the first Africans brought to British colonies in the early seventeenth century to the end of Reconstruction. The authors document the horrors of slavery, particularly in the deep South, and describe the valiant struggles to escape bondage, from dramatic tales of slaves such as William and Ellen Craft to Dred Scott's doomed attempt to win his freedom through the Supreme Court. We see how slavery set our nation on the road of violence, from bloody riots that broke out in American cities over fugitive slaves, to the cataclysm of the Civil War. Along the way, readers meet such individuals as "Black Sam" Fraunces, a West Indian mulatto who owned the Queen's Head Tavern in New York City, a key meeting place for revolutionaries in the 1760s and 1770s. Indeed, the book is filled with stories of remarkable African Americans, from Sergeant William H. Carney, who won the Congressional Medal of Honor for his bravery at the crucial assault on Fort Wagner during the Civil War, to Benjamin "Pap" Singleton, a former slave who led freed African Americans to a new life on the American frontier. With more than one hundred illustrations, Slavery and the Making of America is a gripping account of the struggles of African Americans against the iniquity of slavery
The African roots of Colonial America -- Slavery: from the revolution to the cotton kingdom -- Westward expansion, antislavery, and resistance -- Troublesome property: the many forms of slave resistance -- A hard-won freedom: from Civil War contraband to emancipation -- Creating freedom during and after the war
Includes bibliographical references (p. 246-248) and index
Keywords: Slavery -- United States -- History; African Americans -- History -- To 1863